The TIR‐NBS protein TN13 associates with the CC‐NBS‐LRR resistance protein RPS5 and contributes to RPS5‐triggered immunity in Arabidopsis. (30th May 2021) - Cai, Huiren; Wang, Wei; Rui, Lu; Han, Libo; Luo, Mingyu; Liu, Na; Tang, Dingzhong
Summary: Nucleotide‐binding site (NBS)–leucine‐rich repeat (LRR) domain receptor (NLR) proteins play important roles in plant innate immunity by recognizing pathogen effectors. The Toll/interleukin‐1 receptor (TIR)‐NBS (TN) proteins belong to a subtype of the atypical NLRs, but their function in plant immunity is poorly understood. The well‐characterized Arabidopsis thaliana typical coiled‐coil (CC)‐NBS‐LRR (CNL) protein Resistance to Pseudomonas syringae 5 (RPS5) is activated after recognizing the Pseudomonas syringae type III effector AvrPphB. To explore whether the truncated TN proteins function in CNL‐mediated immune signaling, we examined the interactions between the Arabidopsis TN proteins and RPS5, and found that TN13 and TN21 interacted with RPS5. However, only TN13, but not TN21, was involved in the resistance to P . syringae pv. tomato ( Pto ) strain DC3000 carrying avrPphB, encoding the cognate effector recognized by RPS5. Moreover, the regulation of Pto DC3000 avrPphB resistance by TN13 appeared to be specific, as loss of function of TN13 did not compromise resistance to Pto DC3000 hrcC − or Pto DC3000 avrRpt2 . In addition, we demonstrated that the CC and NBS domains of RPS5 play essential roles in the interaction between TN13 and RPS5. Taken together, our results uncover a direct functional link between TN13 and RPS5, suggesting that TN13 acts as a partner in modulating RPS5‐activated immune signaling, which constitutes a previously unknown mechanism for TN‐mediated regulation of plant immunity. Significance Statement: In this study, we found that the truncated nucleotide‐binding site (NBS)–leucine‐rich repeat (LRR) domain receptor (NLR) protein TN13 associated with the well‐characterized coiled‐coil (CC)‐NBS‐LRR (CNL)‐type NLR protein RPS5 in Arabidopsis. TN13 specifically modulated RPS5‐mediated resistance to Pseudomonas syringae expressing the effector avrPphB, suggesting that TN13 may act as a partner protein in RPS5‐activated immunity. These data uncover a direct link between TIR‐NBS (TN) and CNL proteins, and imply that there is a functional network among diverse NLR proteins regulating plant immunity.